Abdominal Muscle Training Can Enhance Cough After Spinal Cord Injury. (November 2013) - McBain, Rachel A.; Boswell-Ruys, Claire L.; Lee, Bonsan B.; Gandevia, Simon C.; Butler, Jane E.
Background . Respiratory complications in people with high-level spinal cord injury (SCI) are a major cause of morbidity and mortality, particularly because of a reduced ability to cough as a result of abdominal muscle paralysis. Objective . We investigated the effect of cough training combined with functional electrical stimulation (FES) over the abdominal muscles for 6 weeks to observe whether training could improve cough strength. Methods . Fifteen SCI subjects (C4-T5) trained for 6 weeks, 5 days per week (5 sets of 10 coughs per day) in a randomized crossover design study. Subjects coughed voluntarily at the same time as a train of electrical stimulation was delivered over the abdominal muscles via posterolaterally positioned electrodes (50 Hz, 3 seconds). Measurements were made of esophageal (Pes ) and gastric (Pga ) expiratory pressures and the peak expiratory flow (PEFcough ) produced at the 3 time points of before, during, and after the training. Results . During voluntary coughs, FES cough stimulation improved Pga, Pes, and PEFcough acutely, 20-fold, 4-fold, and 50%, respectively. Six weeks of cough training significantly increased Pga (37.1 ± 2.0 to 46.5 ± 2.9 cm H2 O), Pes (35.4 ± 2.7 to 48.1 ± 2.9 cm H2 O), and PEFcough (3.1 ± 0.1 to 3.6 ± 0.1 L/s). Cough training also improved pressures and flow during voluntary unstimulated coughs. Conclusions . FES of abdominal muscles acutely increases mechanical output in coughing in high-level SCI subjects. Six weeks of cough training further increases gastric and esophageal cough pressures and expiratory cough flow during stimulated cough maneuvers.